Happiness: analysis of drivers between Chile and Canada - Mendoza H., Miguel; Gómez C., Benjamín (Estudios de Administración, 2011)
This study attempts to assess the relative importance of different drivers of happiness and their impact in the subjective well being of individuals. It tries to measures factors and conditions that make people report a higher level of happiness. Also, the paper tries to identify how cultural and contextual elements can influence perception of happiness. In order to do this we use conjoint analysis considering as independent variables; level of income, labor stability, security, social networks and level of education for Chile and Canada. The finding suggest that for the case of Chile, Income and job stability are both factor almost equally important to explain a given level of happiness. In the case of Canada income is the most important factor followed by job stability with about half the importance of income.